Combination of Biogas Residues and Bacillus Interactions Stimulates Crop Production and Salinity Tolerance in Sorghum bicolor - Muhammad Waseem Abbasi; Naveed Hussain; Marium Tariq; Muhammad Qasim; Qu Wei; Jianbin Guo; Shoujun Yang; Renjie Dong; Zainul Abideen; Mohamed A. El-Sheikh (Scientifica)
Stress tolerance in cereal crops like Sorghum is important to address food security and land development for saline agriculture. Salinity is considered one of the most devastating abiotic stresses affecting plant growth and yield, specifically in water-scared areas of the world. Biogas residue is a good source of plant nutrients with enriched fertilizer for crop yield and productivity. In this study, seeds were sown in the soil supplied with biogas residues (0% and 5% w/w). After seedling establishment, three Bacillus strains (B26, BS, and BSER) were introduced around the roots of Sorghum. Saline water irrigation started after a week of bacterial inoculation. Sorghum plants were uprooted after 30 days of saline water irrigation. Results indicated that the Bacillus strain and biogas residues showed the highest plant growth in both (0 and 75 mM) salinity levels. Further, this Bacillus strain modulated Sorghum’s secondary metabolites (phenols and flavonoids) and osmoprotectants (proline and soluble sugars) under salinity stress. Reduction in salinity stress demonstrated lower activities of antioxidant enzymes including catalase, ascorbate peroxidase, and superoxide dismutase; however, guaiacol peroxidase activities were enhanced in Bacillus (BS strain) treated plants with biogas residues application. Among the three strains, BS strain demonstrated better results with biogas residues under salinity stress in Sorghum bicolor.